Constraints of value chain in dairy industry in Central Java - Guntoro, Budi (2015)
Dairy value chain is a sequence of dairy production, processing and marketing activities: products pass through all activities of the chain in a certain order and, with each activity, the product gains value. The Objective of the study is to analyze the constraints of value chain in dairy industry in Central Java. The respondents were 90 dairy cattle farmers, and three heads of cooperative as informants. The data were analyzed using descriptive statistical analysis, and explanation. The results showed that formal education level, lack of credit/financial, low of skill, knowledge and quality, weakness in bargaining power,different access to extension service, farm size/number of animal owned, gender constraints risk and uncertainty, low level of technology, service and infrastructure, and market became the value chain constraints in dairy industry in Central Java. Even though livestock keeping among smallholders offers a promising opportunity to combat poverty specially as the demand for animal products such as milk continues to rise, most livestock policies and services tend to favour large-scale production. In order to take advantage of emerging market demands and reduce their poverty, small farmers need access to basic services and technologies as well as policies that take account of their needs and interests